Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.3109/13506120009146437
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of immunoglobulin light chains associated with amyloidosis

Abstract: AL amyloidosis is a fatal disease caused by deposition of immunoglobulin light chains in a fibrillarforin (AL) in various organs. By searching the Kabat database of immunoglobulin sequences using the KabatMan software, we have shown that there is a preponderance of the consensus glycosylation sequon (AsnXxxSer/Thr) in the framework regions of amyloid light chains. We have characterised by computer graphics simulations, NMR spectroscopy and carbohydrate biochemistry the structure and conformation of the oligosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 55 publications
2
43
0
Order By: Relevance
“…Stevens et al 11,12) have reported that more than 80% of amyloidogenic κ1 variable domains are identifiable by the presence of substitutions acquiring a consensus Asn for N-glycosylation. Omtvedt et al 13) have also independently obtained the data suggesting that there is a preponderance of consensus glycosylation sequon in amyloidogenic light chains, to which sialylated and corefucosylated biantennary oligosaccharides mostly with bisecting GlcNAc were preferentially linked. Crystalglobulinemia has been thought to be a different syndrome from AL amyloidosis, however we found an interesting case of crystalglobulinemia, in which the κ chain was glycosylated, suggesting a common molecular mechanism underlying both AL amyloidosis and crystalglobulinemia.…”
Section: Introductionmentioning
confidence: 95%
“…Stevens et al 11,12) have reported that more than 80% of amyloidogenic κ1 variable domains are identifiable by the presence of substitutions acquiring a consensus Asn for N-glycosylation. Omtvedt et al 13) have also independently obtained the data suggesting that there is a preponderance of consensus glycosylation sequon in amyloidogenic light chains, to which sialylated and corefucosylated biantennary oligosaccharides mostly with bisecting GlcNAc were preferentially linked. Crystalglobulinemia has been thought to be a different syndrome from AL amyloidosis, however we found an interesting case of crystalglobulinemia, in which the κ chain was glycosylated, suggesting a common molecular mechanism underlying both AL amyloidosis and crystalglobulinemia.…”
Section: Introductionmentioning
confidence: 95%
“…In these cases, these antibodies may be beneficial or harmful to the host depending on the nature of the antigen (self or non-self) and the particular situation of their action [12,13]. Alternatively, carbohydrates in the variable regions may affect the biological activity [14] or stability [15] of immunoglobulins without altering their affinity for antigens. In line with these observations, it was demonstrated that follicular lymphoma cells produce IgG/IgM with an oligomannosetype oligosaccharide attached to the antigen binding site [16].…”
Section: Introductionmentioning
confidence: 95%
“…Amyloidosis is the end result of a dynamic process in which normally soluble proteins form insoluble fibrils [20]. Glenner et al demonstrated that amyloid fibrils in a patient with amyloidosis were identical to the variable segment of a monoclonal light chain.…”
Section: Discussionmentioning
confidence: 99%